(untitled) (CIPEEX, 2025)
In recent decades, Brazilian eating habits have undergone significant changes, marked by a sharp increase in the consumption of ultra-processed foods. These products are characterized by high amounts of added sugars, sodium, saturated fats, and chemical additives, in addition to having low nutritional density. Among ultra-processed foods, soft drinks stand out as one of the most widely consumed and readily available items. High palatability, aggressive marketing, and affordable prices are factors that favor their regular consumption (RC) across different age groups and social contexts. In contrast, dietary patterns based on the RC of fresh or minimally processed foods, such as fruits and vegetables, offer numerous health benefits. These foods are rich sources of vitamins, minerals, fiber, and bioactive compounds that play a protective role against chronic noncommunicable diseases and strengthen the immune system. In addition, scientific evidence shows that a balanced diet is associated with improved quality of life and increased productivity. In the context of the Federal Network for Professional, Scientific, and Technological Education (RFEPCT), composed of teachers and administrative technicians in education (TAE), understanding food consumption patterns takes on special relevance. These professionals, often exposed to high levels of stress due to workload, academic and administrative demands, and the institutional environment, may have their health directly impacted by their eating habits. Given this scenario, the objective of this study was to investigate the association between the RC of soft drinks and the consumption of healthy foods among RFEPCT employees. The research was conducted online in 2022, after approval by the Research Ethics Committee (No. 5.270.596). The sample consisted of 1,563 RFEPCT teachers and TAE, distributed across different regions of Brazil. Sociodemographic variables were collected, in addition to dietary information obtained from the questionnaire used in the PENSE. For this study, RC was that performed on five or more days per week. The effect measure used was the Prevalence Ratio, accompanied by its respective 95% confidence intervals (95% CI). The results showed that RC of soft drinks was positively associated with the Southeast (p = 0.002) and Midwest (p = 0.001) regions, suggesting that residents of these locations are more likely to consume soft drinks regularly. A negative association was found with the 48-60 age group (p = 0.020), indicating that older individuals tend to reduce their consumption. Regarding RC of fresh fruit, a positive and statistically significant association was observed (p < 0.001). However, no significant associations were found for the variables female gender (p = 0.790), teaching position (p = 0.108), and consumption of vegetables (p = 0.054). These findings suggest that the pattern of consumption of soft drinks and healthy foods among civil servants is influenced more by regional and age factors than by gender or position. The data indicate that the dietary profile of Federal Network civil servants is marked by sociodemographic inequalities, which reinforces the need for specific strategies to promote healthier habits, especially in regions and groups with higher consumption of ultra-processed foods.